Vrednote mladih - Hribar, Spomenka (Družboslovne razprave, 1999)
The essay resumes the author's lecture in a course on actual subjects for students and intelectuals, held at the Faculty of Theology in Ljubljana, November 19th, 1985. The author mediates over values, the basic value in particular, which at present time has been most clearly expressed in the Program of the former Communist Party of Yugoslavia: "Nothing which has been created is so sacred that it could not be surmounted, and would not give way to what is more progressive, more free, more human." If, however, nothing is as sacred... everything is at disposal. The above sentence is defined by the author as an example, as the fundamental sentence of nihilism of our time: Everything and everybody is available for various political options. The author ascertains that the talk only about values that are lacking... is insufficient. The basic question is the creation of a new sacred world. Because equalization of the ideologically consecrated and holy is what led to a general manipulation, when nothing is intangible - sacred. Neither the human being. Nor the holy.
Keywords: vrednote; mladina